Perioperative Protocols in Colorectal Surgery - DeBarros, Mia; Steele, Scott R. (Clinics in Colon and Rectal Surgery, 2013)
The reduction in health-care expenditures and more efficient use of medical resources are now overriding health policy priorities with the two-pronged goal of improving patient outcomes while decreasing overall cost. Current reports show colorectal surgery accounting for 25% of all operative complications and an average length of stay of 8 to 12 days for a standard elective colon resection. To combat this, Kehlet and colleagues introduced a concept of enhanced recovery after surgery (ERAS) or fast-track pathways, with the goal of using current evidence and multimodal therapies to decrease surgical stress, enhance postoperative recovery, and reduce length of stay. The benefits, safety, and cost-effectiveness of fast-track protocols are validated in multiple randomized controlled trials. In this review, the authors focus on the evidence regarding fast-track pathways, use of minimally invasive surgery and its role in fast-track pathways, newer perioperative interventions, and future directions.
Keywords: colorectal surgery; perioperative protocols; fast-track surgery; enhanced recovery after surgery; ERAS